A critical introduction to law and literature - Dolin, Kieran (Cambridge University, 2013)
Despite their apparent separation, law and literature have been closely linked fields throughout history. Linguistic creativity is central to the law, with literary modes such as narrative and metaphor infiltrating legal texts. Equally, legal norms of good and bad conduct, of identity and human responsibility, are reflected or subverted in literature's engagement with questions of law and justice. Law seeks to regulate creative expression, while literary texts critique and sometimes openly resist the law. Kieran Dolin introduces this interdisciplinary field, focusing on the many ways that law and literature have addressed and engaged with each other. He charts the history of the shifting relations between the two disciplines, from the open affiliation between literature and law in the sixteenth-century Inns of Court to the less visible links of contemporary culture. Each chapter is organized around close analysis of a famous trial or literary-legal encounter. The wide resonance of such trials illuminates the cultural centrality of law, and the social responsiveness of literature.